Acetylation impacts Fli‐1‐driven regulation of granulocyte colony stimulating factor. Issue 10 (16th August 2016) - Lennard Richard, Mara L.; Brandon, Danielle; Lou, Ning; Sato, Shuzo; Caldwell, Tomika; Nowling, Tamara K.; Gilkeson, Gary; Zhang, Xian K.
Abstract : Fli‐1 is a dominant factor that regulates the expression of G‐CSF in endothelial cells. Fli‐1 binds to the G‐CSF promoter after LPS stimulation in human and murine endothelial cells. Transcriptional activation of the promoter is influenced by Fli‐1 binding to the proximal region of the promoter and acetylation. Abstract : Fli‐1 has emerged as a critical regulator of inflammatory mediators, including MCP‐1, CCL5, and IL‐6. The cytokine, granulocyte colony stimulating factor (G‐CSF) regulates neutrophil precursor maturation and survival, and activates mature neutrophils. Previously, a significant decrease in neutrophil infiltration into the kidneys of Fli‐1 +/‐ lupus‐prone mice was observed. In this study, a significant decrease in G‐CSF protein expression was detected in stimulated murine and human endothelial cells when expression of Fli‐1 was inhibited. The murine G‐CSF promoter contains numerous putative Fli‐1 binding sites and several regions within the proximal promoter are significantly enriched for Fli‐1 binding. Transient transfection assays indicate that Fli‐1 drives transcription from the G‐CSF promoter and mutation of the Fli‐1 DNA binding domain resulted in a 94% loss of transcriptional activation. Mutation of a known acetylation site, led to a significant increase in G‐CSF promoter activation. The histone acetyltransferases p300/CBP and p300/CBP associated factor (PCAF) significantly decrease Fli‐1 specific activation of the G‐CSF promoter. Thus, acetylation appears to be an important mechanism behind Fli‐1 driven activation of the G‐CSF promoter. These results further support the theory that Fli‐1 plays a major role in the regulation of several inflammatory mediators, ultimately affecting inflammatory disease pathogenesis.